Implementation Of An Open Ended Learning Model Assisted With The Mentimeter Application To Improve Students' Cognitive Learning Outcomes - Rosmiati, Sely; Maftuh, Bunyamin (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2024)
This research was motivated by the low cognitive learning outcomes of some students in thematic learning. An alternative learning method for students' low cognitive learning outcomes is to apply an open ended learning model assisted by the mentimeter application. This research aims to determine the average difference in cognitive learning outcomes of class VI students in thematic learning using an open ended learning model assisted by the mentimeter application and image media. The population of this study were all class VI students at SDN Sapan for the 2022/2023 academic year. The samples taken were class VI A and class VI B using purposive sampling technique. Data collection techniques are carried out using tests and observations. The data analysis technique uses an independent t-test with a significance level of 5% with the hypothesis that there is a difference in the average increase in cognitive learning outcomes between students who follow the open ended learning model assisted by the mentimeter application and students who follow the open ended learning model assisted by image media. The research results obtained: Cognitive learning results before and after implementing the open ended learning model assisted by the mentimeter application improved. Cognitive learning outcomes before and after implementing the open ended learning model assisted by image media did not improve. There is no difference in the average increase in cognitive learning outcomes between students who follow the open ended learning model assisted by the mentimeter application and students who follow the open ended learning model assisted by image media.